Installation for photocatalytic water purification from organic pollution in the flow reactor - A. V. Baglov; A. A. Radionov; E. B. Chubenko; V. A. Zaycev; V. E. Borisenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
A laboratory installation for photocatalytic water purification from organic pollutants has been developed. It includes a flow reactor, replaceable light sources of visible and ultraviolet ranges, indicator and control units. The installation provides testing at room temperature of the efficiency of photocatalysts, deposited on the solid and perforated flat substrates at a flow rate of 0.2-1.2 l/min of purified water.